2016
DOI: 10.1016/j.tjog.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Medical nutrition therapy for pregnant women with gestational diabetes mellitus—A retrospective cohort study

Abstract: MNT can reduce the incidence of pregnancy complications, increase the exclusive breastfeeding rate, and improve pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…Food exchange tables is a great tool to enhance individualization of dietary advice as it empowers patients to add variety to the prescribed meal plan while at the same time ensuring a balanced intake of all necessary nutrients. A retrospective cohort study showed reduced adverse events in the group receiving MNT using the food exchange tables as compared to the group not receiving MNT [59].…”
Section: Interventions To Enhance Healthy Eating and Meal Planningmentioning
confidence: 99%
“…Food exchange tables is a great tool to enhance individualization of dietary advice as it empowers patients to add variety to the prescribed meal plan while at the same time ensuring a balanced intake of all necessary nutrients. A retrospective cohort study showed reduced adverse events in the group receiving MNT using the food exchange tables as compared to the group not receiving MNT [59].…”
Section: Interventions To Enhance Healthy Eating and Meal Planningmentioning
confidence: 99%
“…MNT has been identified as the fundamental approach in the prevention and management of GDM. This therapy should ideally be developed, implemented and monitored by an RD or nutritionist [126128].…”
Section: Medical Nutrition Therapy For the Management Of Gestational mentioning
confidence: 99%
“…Likewise, similar outcomes were produced by an intensive MNT programme and routine obstetric care in insulin use, prematurity, macrosomia, low birth weight, and intrauterine death 38 . MNT counselling produced superior outcomes in maternal weight, rates of adverse events, and exclusive breast feeding than a no MNT control 37 . Similarly, an intensive MNT programme produced better outcomes in rates of perinatal complications, preeclampsia, maternal hospitalisations, neonatal intensive care unit admissions, and had no neonatal deaths compared with routine obstetric care 38 .…”
Section: Effectiveness Of Medical Nutrition/diet Therapy Interventionsmentioning
confidence: 85%
“…Nine studies examined medical nutrition/diet therapy programmes which involved low-glycaemic index (LGI) diet [31][32][33] , oat bran plus routine diet for gestational diabetes 34 , dietary approaches to stop hypertension (DASH) diet that is rich in fruits, vegetables, whole grains and low-fat diary products 35 , 3-day intensive diet therapy 36 , medical nutrition therapy counselling [37][38][39] .…”
Section: Medical Nutrition/diet Therapy Interventionsmentioning
confidence: 99%
See 1 more Smart Citation